Model Blended Learning Pada Materi Bilangan Bulat; Eksperimentasi Pada Siswa Kelas VII SMP Negeri 6 Tondano - Nafila Farina Gaib; Ichdar Domu; Rosiah J. Pulukadang (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study examined the average student mathematics learning outcomes when the Blended Learning Model was applied to learning integer material. The study design used was: Posttest Only Control Group Design. The population in this study was all of class VII at SMP Negeri 6 Tondano. In contrast, the samples in this study were class VII B, with 21 students as the experimental class and class VII A as the control class with 21 students. This study's analysis showed that the experimental class's average posttest score was 84,76, while the average posttest score for the control class was 74,28. The study results were analyzed using the T-test statistic at s significant level of 0,05, namely Tcount = 3,636 > Ttable = 1,725, so that H0 was rejected and H1 was accepted. The Blended Learning Model can improve student learning outcomes based on these results.